Influence of Learners’ Readiness and Physical Facilities on Transition of Learners with Visual Impairment from Integrated Pre-primary to Primary Schools in Narok County, Kenya - Shinali, Maryconsolata; Koech, Peter Kibet; Kimani, Cecilia (Journal of Education, Society and Behavioural Science, 2022)
Transition of pre-primary learners with visual impairment from integrated pre-primary to primary schools in Narok County has been low. Thus, the study assessed school dynamics influencing transition of learners with visual impairment from integrated pre-primary to primary schools in Narok County, Kenya. The study was based on the Ecological Systems Theory and Transition Theory. The study employed mixed methods approach and in turn used concurrent triangulation research design. The target population consisted of 16 headteachers, 3 Educational Assessment and Resource Centre (EARC) officers and 208 teachers and 160 learners with visual impairment all totalling to 387. The study adopted the Krejcie and Morgan (1970) sample size determination formula where a sample size of 266 respondents was sampled. The study used purposive and stratified sampling method to select the sample. 15 headteachers and three EARC Officers were sampled using purposive sampling. Stratified random sampling method was used to select 135 teachers while 113 learners were selected using simple random sampling. Questionnaires were used to collect data from teachers, interview guides were used to collect data from headteachers and EARC Officers while an observation checklist was used to collect data from the learners. Pilot testing of the instrument was done on 2 headteachers, one EARC officer, 12 teachers and 5 learners with visual impairment from the neighbouring Bomet County. Validity was established through expert judgement. Reliability was established using test re-test technique and reliability index, r = 0.867 was determined using Cronbach Alpha Method. The study established that learners’ readiness and physical facilities influence transition of learners with visual impairment from integrated pre-primary to primary schools. The study recommends that Ministry of Education should redesign the teacher training curriculum to encompass components of special needs education to equip them with skills to handle and teach learners in integrated school microsystems. I would recommend that Ministry of Education should also allocate more funds to schools to enable the school management to provide adequate, but suitable physical facilities for learners with visual impairment.
Keywords: Visual impairment; pre-primary; learners’ readiness; learners with visual impairment; physical facilities